2020
DOI: 10.1371/journal.pone.0233952
|View full text |Cite
|
Sign up to set email alerts
|

Development of cellulose-based conductive fabrics with electrical conductivity and flexibility

Abstract: This study aimed to produce cellulose-based conductive fabrics with electrical conductivity and flexibility. Bacterial cellulose (BC) and three chemical cellulose (CC), namely methyl cellulose (MC), hydroxypropyl cellulose (HPMC) and carboxymethyl cellulose (CMC) were in situ polymerized with aniline and the four conductive cellulose fabrics were compared and evaluated. Matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy analysis confirmed that three CC-PANI composites displayed longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Generally, a sample with good crease recovery can return to its original state without being damaged (Kim et al 2020a). Thus, it can be assumed that a sample with a high crease recovery value has good durability (Kim et al 2020a). According to Fig.…”
Section: Crease Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a sample with good crease recovery can return to its original state without being damaged (Kim et al 2020a). Thus, it can be assumed that a sample with a high crease recovery value has good durability (Kim et al 2020a). According to Fig.…”
Section: Crease Recoverymentioning
confidence: 99%
“…BC is an eco-friendly cellulose material produced by Acetobacter xylinus (Kim et al 2020a). Since BC is made of a fibrous three-dimensional nanostructure, it has excellent advantages as a bio-leather: It possesses high purity, high crystallinity and polymerization degree, and good water-holding capacity (Kim et al 2020b); Altering the fermentation conditions can result in BC with excellent moldability, biodegradability, and biocompatibility (Song et al 2020); Moreover, unlike animal leather, additional processes such as tanning and graining are not necessary for BC bio-leather.…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR spectra are demonstrated in Fig 5, and the characteristics of the BC-COF peaks are listed in Table 1. As shown in Fig 5, the FT-IR spectra of BC-COF and original BC displayed peaks at 3347 cm -1 and 3448 cm -1 , respectively, which were attributed to the -OH stretching vibrations of the hydroxyl groups of cellulose and coffee [48][49][50]. These peaks indicated that the chemical structure of BC remained unchanged after dyeing with coffee [2].…”
Section: Surface Characterizations Of Bc-cof Bio-leathermentioning
confidence: 90%
“…20 The naturally-occurring cellulose is in the form of nanofibers with linear molecular chains highly aligned together, thus gaining outstanding mechanical robustness that is comparable to Kevlar fibers. 19 The structural hierarchy of cellulose at multi-length scale ranging from the molecular level to nanoscale 21 chemically modifiable 21 chemically modifiable 22 Flexibility good 23 good good 24 Raw materials price low cost 20 low cost 20 low cost 20…”
Section: Introductionmentioning
confidence: 99%